Antinociceptive and anti-inflammatory actions of curcumin and nano curcumin: a comparative study - Mojdeh Mohammadi; Farshid Sangin Abadi; Rasool Haddadi; Amir Nili-Ahmadabadi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Pain and inflammation can be treated by various therapies that for the most part are not effective and can result in adverse effects. The current study was proposed to compare the antinociceptive and anti-inflammatory actions of curcumin and nano curcumin in rats. Experimental approach: Rats were randomly allocated into ten groups of six for formalin and tail-flick tests including the control group, curcumin and nano curcumin groups (20, 50, 100 mg/kg), morphine group (10 mg/kg), naloxone + 100 mg/kg curcumin group, and naloxone + 100 mg/kg nano curcumin group. There were nine groups for the carrageenan test. Groups 1-7 were the same as the previous division; groups 8 and 9 received 10 mg/kg diclofenac and 1% carrageenan, respectively. Findings/Results: All doses of nano curcumin significantly decreased the paw-licking time in both phases of the formalin test. In the tail-flick test, curcumin 100, nano curcumin 100, naloxone + curcumin 100, and naloxone + nano curcumin 100 showed significant analgesic effects compared to the control group. In the paw edema test, at 180 s after injection, curcumin (50 and 100 mg/kg) and all doses of nano curcumin significantly inhibited carrageenan-induced edema. Myeloperoxidase activity and lipid peroxidation decreased at doses of 50 and 100 mg/kg of curcumin but at three doses of nano curcumin (20, 50, and 100 mg/kg). Conclusion and implication: In conclusion, our results suggest that the nanoemulsion formulation of curcumin can be efficient in reducing pain and especially inflammation in lower doses compared to the native form of curcumin.